Development of an electrochemical sensor based on carbon black for the detection of cannabidiol in vegetable extracts. Issue 2 (13th November 2020) - Cirrincione, Marco; Zanfrognini, Barbara; Pigani, Laura; Protti, Michele; Mercolini, Laura; Zanardi, Chiara
Abstract : A glassy carbon electrode chemically modified with a carbon black coating is proposed here for the rapid and portable determination of cannabidiol (CBD) in a commercial Cannabis seed oil and in fibre-type Cannabis sativa L. leaves. Abstract : A glassy carbon electrode chemically modified with a carbon black coating is proposed here for the rapid and portable determination of cannabidiol (CBD) in a commercial Cannabis seed oil and in fibre-type Cannabis sativa L. leaves. The mechanism of CBD oxidation was studied in relation to simpler phenyl derivatives bearing the same electroactive group, namely resorcinol and 2-methylresorcinol. These molecules also allowed us to determine the best conditions for the electrochemical detection of CBD, as to the pH value and to the best solvent mixture to use. Carbon black was chosen among nanostructured carbon-based materials owing to its outstanding features as an electrode modifier for analyte detection. The performance of the modified electrode was determined by flow injection analyses of standard solutions of CBD, obtaining a linear correlation between the oxidation current and the analyte concentration; the sensor response is characterised by suitable repeatability and reproducibility. The analysis of commercial products by the standard addition method allowed us to ascertain the accuracy of the sensor for the detection of CBD in real samples.